110 Clinical Presentations of Adult and Pediatric SARS-CoV-2-Positive Cases in a Community Cohort. (April 2022) - Rankin, Danielle A; Yanis, Ahmad; Howe, Harrison; Fernandez, Kailee; Talj, Rana; Chappell, James D.; Speiker, Andrew; Howard, Leigh; Halasa, Natasha B.
Abstract : OBJECTIVES/GOALS: The spectrum of disease caused by SARS-CoV-2 ranges from asymptomatic detection to severe illness, with varying presentations by age. Therefore, we aimed to compare the clinical characteristics between children and adults with SARS-CoV-2. METHODS/STUDY POPULATION: From March 20, 2020, to August 18, 2021, we conducted SARS-CoV-2 surveillance in individuals from metropolitan Nashville, TN. Children with multisystem inflammatory syndrome were excluded. Analyses were restricted to individuals with SARS-CoV-2 infection confirmed by detection of viral RNA in nasal specimens using reverse-transcription quantitative polymerase chain reaction (RT-qPCR) and/or by detection of serum IgG to the SARS-CoV-2 spike and nucleocapsid proteins using enzyme-linked immunosorbent assay (ELISA). Those with negative RT-qPCR results, but a positive ELISA within 4-6 weeks of symptom onset, were classified as SARS-CoV-2 positive. Clinical characteristics between children and adults were compared with Pearson's chi square. Illness duration was compared using Kaplan Meier estimators. RESULTS/ANTICIPATED RESULTS: Overall, 426/826 (49%) individuals (children: 57 [13%); adults: 369 [87%]) were SARS-CoV-2 positive, with median ages of 12 and 41 years, respectively. Most individuals were female (54%) and white, non-Hispanic (79%). Compared to adults, children were more likely to be asymptomatic (children: 16% vs. adults: 5%; p=0.001). In contrast, symptomatic adults were more likely to report cough (71% vs. 56%), wheezing (21% vs. 8%), shortness of breath (45% vs. 19%), ageusia (67% vs. 23%), and anosmia (64% vs 27%) than symptomatic children (p<0.05). Mean illness duration was shorter in children than adults: 7 days (95% CI: 5.1, 8.9) vs. 14 days (95% CI: 12.4, 15.0), respectively. A total of 5% (18/352) of adults reported symptoms lasting ? 4 weeks (range: 31-96 days), whereas all symptoms in children resolved by 31 days. DISCUSSION/SIGNIFICANCE: Overall, children with SARS-CoV-2 present with a shorter and milder disease course compared to adults. Further studies are needed to understand SARS-CoV-2 illness severity across the lifespan.